Gen Z’s Muslim Customer Decision in Online Shopping: Estimating The Effects of Business Ethics and Prices Consciousness - Eka Puteri, Hesi; Arinda, Niyara; Fonda, Ayu; Hidayat, Faisal; Ridhah, Habibatur (ICIEFS Proceeding, 2024)
. Online shopping behavior among young Muslim customers is indeed interesting to discuss, especially because this segment is unique. They are very aware of trends, familiar with social media, but have a limited budget for shopping. This study aims to predict the effects of Business Ethics and Prices Consciousness on Gen Z’s Muslim customer decisions in adopting online shopping. This study is quantitative research with cross-sectional data based on a survey of 100 young Muslim active customers in West Sumatra Indonesia in 2024. These findings conclude that Gen Z’s Muslim Online-shopping decisions are influenced positively by price consciousness with estimated coefficients of 0.504 (p-value = 0.001), while Business Ethics shows no effect. The dominance of rational motives from Gen Z’s Muslim customers while doing online shopping has implications for policies for industry actors to be able to adjust relevant market driving strategies in developing the youth market segment. Young Muslim consumers claim to prefer online shopping because of rational reasons behind it such as discount offers attract consumer interest, transparent prices on the website, and also prices are more economical.